Recent marine carbonate hardgrounds at Abu Dhabi: towards a better understanding of ‘hidden hardgrounds’ in the geological past - Chen, Chao; Zhong, Hanting; Wang, Xia; Ning, Meng; Wang, Xinyu; Wang, Han; Tang, Ruifeng; Hou, Mingcai (Frontiers in Marine Science, 2025)
Marine hardgrounds are common features during the Phanerozoic and hold significant sedimentological and economic importance. Intriguingly, previous reports of marine hardgrounds are concentrated in Calcite Seas, despite elevated seawater CaCO3 saturation in Aragonite Seas. This bias remains unclear in origin and requires more hardground information, especially from Aragonite Seas, for clarification. Well-developed Holocene marine hardgrounds at Abu Dhabi provide such a good opportunity. This study focused on a widespread and well-developed Holocene marine hardground layer at Abu Dhabi and analyzed its chronostratigraphy, petrology, mineralogy, and geochemistry. The results show that the studied hardground layer can be divided into lower and upper parts, characterized by planar upper surface and no borings nor encrustations. The lower part (with a 14C age of 6945−6368 cal yrs BP) formed during a sea-level transgression, and is laterally traceable along both a seaward and a landward direction. The upper part (with a 14C age of 5871−5452 cal yrs BP) formed during following sea-level transgression and/or stillstand, and disappears along a landward direction. Compared with the lower part, the upper hardground part is higher in δ13Ccarb and δ18Ocarb, supporting formation within more evaporated seawater settings depositing more high-Mg calcite. Both parts consist mainly of aragonite and high-Mg calcite in both carbonate grains and intergranular early-marine cement, but the lower hardground part contains more protodolomite within the early-marine cement. Moreover, an inverse relation in contents indicates a diagenetic transition from aragonite to dolomite during hardground formation and early diagenesis. Further, in combination with previous studies, the findings of this study confirm the rapidity, lateral diachronicity, and composite nature of Holocene marine hardgrounds with mineralogy controlled by sea-level changes. Similar hardgrounds may also be well developed in ancient records (especially in Aragonite Seas like the modern ocean), but be ignored due to lack of recognizable features (e.g., boring, irregular upper surfaces, Fe-Mn encrustation) and mineral recrystallization. These “hidden hardgrounds” and their composite formation by diachronous parts have implications for sequence stratigraphy and hydrocarbon exploration using hardgrounds in stratigraphic correlation.